Lower urinary tract reconstruction following a cystectomy: experience and results in 20 patients using the "Studer" orthotopic ileal bladder substitution - Saidi, S; Ivanovski, O; Petrovski, D; Kuzmanoski, M; Stavridis, S; Banev, S; Popov, Z (My University, 2008)
To analyze the outcome, complications and functional results in patients undergoing bladder substitution with the Studer continent urinary pouch.